Assessment of Grey Forecasting Model: Study Case for Electrification Rate in Indonesia from 2012 to 2021 - Mufrida Zein; Muhammad Ghalih; Rina Pebriana (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
In 2021, Indonesia was 99.45% electrified. That year's aim was 100%. Due of Indonesia's 17,000 islands, electrifying rural settlements is tough. Depending on network size and demand, Indonesia's energy mix varies, however it often includes coal. After adopting the Paris Climate Agreement, Indonesia vowed to increase renewable energy to 23% by 2025. Indonesia's renewable energy production has increased. The government expects coal to be important in coming decades. The GM (1, 1) model of Grey theory was used to estimate Indonesia's electrification rate from 2012 to 2021. The model's average residual error is above 5%, according to the calculation. Indonesia's electrification rate is expected to grow annually. According to the trials, the recommended technique boosts the forecasting accuracy of the original Grey models and gives Indonesia a helpful reference for designing the action plan.